L’insémination artificielle chez la chèvre - MANAL, MILOUDI (My University, 2020)
In seasoned goat breeds, methods of improving semen production and preservation must take into account the influence of the environment and in particular of the photoperiod. Through the function it exerts on the regulation of gonadal development, it indirectly contributes to the control of sexual behavior and sperm production, both quantitatively and qualitatively. The use of photoperiodic treatments therefore constitutes an effective tool for increasing the production of doses of sperm intended for artificial insemination during the male goat's reproductive career. In order to optimize the production and the quality of the semen, a preliminary selection of the males is however necessary. A specific problem in the storage of goat semen is the deleterious effect of seminal plasma on the viability of sperm after freezing / thawing, mainly when diluted in media based on milk or egg yolk. The protein responsible for this effect is an enzyme secreted by the bulbo-urethral glands belonging to the pancreatic lipase family and which has a double lipase and phospholipase activity. Preservation of semen in a liquid state, inexpensive, is a complement to cryconservation to develop artificial insemination on a large scale. But the decrease in fertility after 12 hours of storage hinders the use of this technique. Freezing methods currently available differ in several aspects. The most effective include washing the semen to remove seminal plasma upon collection. The methods of estrus and ovulation control allowing the formation of homogeneous batches of females with regard to their reproduction have favored the development of artificial insemination (AI) in small ruminants and in particularly in goats. This method is now used to intensify production within the framework of programs intended to improve the genetic potential of breeds producing milk, meat or hair. Compared to natural breeding, AI allows an increase in the number of offspring and therefore the number of males as well as a spatio-temporal dissociation between the collection of the semen and its use. These advantages allow the evaluation, selection of males and comparison of the genetic merit of their offspring through genetic links from AI males. This article summarizes the main aspects of semen production and storage in the goat.